Rola samorządów w systemie wspierania napływu bezpośrednich inwestycji zagranicznych - Stapiński, Rajmund (PRAWO i WIĘŹ, 2024)
The author aimed to identify the main motives of foreign direct investment inflows and correlate them with the national system of their support. The paper included a classification of forms of legal, economic and institutional support for investors. The consideration was aimed at indicating the role of local government units in servicing entrepreneurs, considering Poland as an investment destination.